2009
DOI: 10.1016/j.conb.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Function follows form: ecological constraints on odor codes and olfactory percepts

Abstract: SummarySensory system function has evolved to meet the biological needs of organisms, but it is less often regarded that sensory system form has by necessity evolved to contend with the stimulus. For an olfactory system extracting meaningful information from natural scents, the ecological milieu presents unique problems. Recent studies provide new insights into the perceptual and neural mechanisms underlying how odorant elements are assembled into odor wholes, how odor percepts are reconstructed from degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…It may be that following fewer encounters with the odor the rats learned to ignore a more general quail odor, reducing the likelihood of the eggs attracting attention after their introduction. Black rats should have the olfactory capability to distinguish between quail odor and egg odor (25), but generalizing may be less cognitively costly and adequate for normal foraging activities (16,26). That rats required little spatial reinforcement to filter an unrewarding odor into their olfactory background suggests their cognitive processes are adapted for optimizing foraging efficiency in situations where encountering novel food is common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that following fewer encounters with the odor the rats learned to ignore a more general quail odor, reducing the likelihood of the eggs attracting attention after their introduction. Black rats should have the olfactory capability to distinguish between quail odor and egg odor (25), but generalizing may be less cognitively costly and adequate for normal foraging activities (16,26). That rats required little spatial reinforcement to filter an unrewarding odor into their olfactory background suggests their cognitive processes are adapted for optimizing foraging efficiency in situations where encountering novel food is common.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian predators live in a rich olfactory world, able to detect and recognize immense numbers of odors and distinguish minute differences in complex mixtures (13,14). Such capabilities should hinder efficient foraging unless superfluous olfactory information can be quickly disregarded (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors may influence the perception of a mixture such as chemical structure, intensity or salience of the components and mixture complexity (Gottfried 2009;Riffell 2012;Thomas-Danguin et al 2014). Interactions between odor molecules occur at the receptor level of the olfactory system (e.g., Bell et al 1987;DuchampViret et al 2003;Kay et al 2003), in the olfactory bulb (antennal lobe in insects; e.g., Linster et al 2001;Deisig et al 2006;Dulac 2006) and/or in higher brain areas (e.g., Boyle et al 2009;Gottfried 2010;Wilson and Sullivan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…bee, catfish, human, spiny lobster, moth and rat), with different approaches (e.g. [9][10][11][12][13][14][15][16]). For instance, data in human adults revealed that a mixture of two odorants (AB), one smelling like strawberry (A: ethyl isobutyrate) and the other like caramel (B: ethyl maltol), generates the configural perception of a pineapple odour at a specific ratio of A/B [17,18].…”
Section: Introductionmentioning
confidence: 99%